Essential oil composition of Acca sellowiana (O. Berg.) Burret - Rotman, Alicia Dora (2002)
Essential oils of Acca sellowiana (O. Berg.) Burret was examined by GC and GC/MS. The main components for oil were, spathulenol (24.4%), δ-cadinene (9.6%), β-terpineol (8.7%) and ß-caryophyllene (8.1%).